ODRL Profile for Expressing Consent through Granular Access Control Policies in Solid - Pandit, Harshvardhan (My University, 2021)
Solid, the emerging technology for organizing data in decentralized stores, relies on a simple authorization mechanism for granting access to data. Solid's personal online datastores (Pods) are ideal for keeping personal data, as they allow individuals to represent the access permissions in a very simple manner using Access Control Language (ACL) expressions. Whereas these expressions suffice for yes/no and read/write permissions, they cannot represent more complex rules nor invoke regulation-specific concepts. This paper describes an extension of the ACL language and algorithm to implement consent and data requests. The extension is based on the Open Digital Rights Language (ODRL) policy language, which allows expressing rich rules, and the Data Privacy Vocabulary (DPV), which permits invoking privacy and data protection-specific terms.
Workshop on Consent Management in Online Services, Networks and Things (COnSeNT)
ACCEPTED
Virtual
Keywords: Access control; Consent; Data protection; Decentralized datastores; Privacy; DPV; GDPR; Regulatory compliance; Access Control; CONSENT; SEMANTIC WEB; Solid